Thermal Modifications of Root Transparency and Implications for Aging: A Pilot Study. Issue 1 (23rd August 2013) - Gibelli, Daniele; De, Danilo; Rossetti, Francesca; Cappella, Annalisa; Frustaci, Michela; Magli, Francesca; Mazzarelli, Debora; Mazzucchi, Alessandra; Cattaneo, Cristina
Abstract Root transparency has proven to be related to age and has been considered by different odontological methods for age estimation. Very little is known concerning possible variations of root transparency with heat, although the applicability of the method to burnt remains depends on the possible modifications of this specific variable. This pilot study presents the results of an experiment performed on 105 teeth obtained from dental patients and autopsy material, heated in an industrial oven at 50°C, 100°C, 150°C and 200°C. Root transparency was measured before and after the charring experiment. The heating process proved to radically modify root transparency, which decreased in 20% of samples at 50°C, in 34.6% at 100°C, in 50% at 150°C, in 77% at 200°C. The overall correlation index (CI) between decrease in root transparency and increase in temperature amounted to 0.96. These results show that heat may modify root transparency and suggest caution in using methods based on root transparency for age estimation.